2021
DOI: 10.1111/1759-7714.14063
|View full text |Cite
|
Sign up to set email alerts
|

Association between pretreatment neutrophil‐to‐lymphocyte ratio and immune‐related adverse events due to immune checkpoint inhibitors in patients with non‐small cell lung cancer

Abstract: Background: Immune checkpoint inhibitors (ICIs) have revolutionized the treatment of advanced or recurrent non-small cell lung cancer (NSCLC). They cause immunerelated adverse events (irAEs), but the underlying mechanisms and predictors remain to be fully elucidated. In this retrospective study, we investigated the association between pretreatment neutrophil-to-lymphocyte ratio (NLR) and the occurrence of irAEs. Methods: The study involved 115 patients with NSCLC who started ICI-only treatment in our hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 34 publications
1
27
0
Order By: Relevance
“…Lastly, a recent retrospective analysis of 115 patients with NSCLC treated with PD-(L)1 inhibitors showed that a low pretreatment NLR may predict for the occurrence of immune-related adverse events (irAEs); whether dNLR changes may further correlated with the risk of irAE develop needs to be assessed in future studies. 25 There are an increasing number of continuous biomarkers associated with ICI efficacy, including PD-L1 expression, infiltrating immune cells, and TMB. [26][27][28] Likewise, dNLR appears to behave in a continuous fashion, both in terms of therapeutic outcomes to ICI, and also with the tumor immunophenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, a recent retrospective analysis of 115 patients with NSCLC treated with PD-(L)1 inhibitors showed that a low pretreatment NLR may predict for the occurrence of immune-related adverse events (irAEs); whether dNLR changes may further correlated with the risk of irAE develop needs to be assessed in future studies. 25 There are an increasing number of continuous biomarkers associated with ICI efficacy, including PD-L1 expression, infiltrating immune cells, and TMB. [26][27][28] Likewise, dNLR appears to behave in a continuous fashion, both in terms of therapeutic outcomes to ICI, and also with the tumor immunophenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Common hematological indicators, such as inflammatory factors, tumor markers and cell free DNA (cfDNA) have gradually been shown to play important roles in the microenvironment of NSCLC. There is considerable evidence regarding neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) as prognostic markers in NSCLC patients treated with immunotherapy (11)(12)(13) and targeted therapy (14,15). However, few studies have explored the significance of these indicators in the alectinib treatment of ALK-positive NSCLC (16).…”
Section: What Is the Implication And What Should Change Now?mentioning
confidence: 99%
“…A low NLR re ects a low peripheral neutrophil count and high lymphocyte count, indicating maintenance of the immune system. We have previously reported that a low pretreatment NLR may be a predictive factor for the occurrence of irAEs with ICI monotherapy [4]. Despite the effect of cytotoxic chemotherapy on neutrophil and lymphocyte counts, this study showed that a low pretreatment NLR is a useful predictive factor for irAE development in ICI plus platinum agent therapy, similar to ICI monotherapy.…”
Section: Discussionmentioning
confidence: 52%
“…Furthermore, large case series studies of NSCLC and other tumors have shown that irAE development is associated with improved survival outcomes [3]. Therefore, numerous previous studies on risk factors for the development of irAEs have been conducted, and several risk factors were reported, such as a low neutrophil-to-lymphocyte ratio (NLR), high body mass index (BMI), high serum albumin (ALB) level, and low Eastern Cooperative Oncology Group (ECOG) performance status (PS) [4][5][6][7][8].…”
mentioning
confidence: 99%